Land grabs and labour: Vietnamese workers on rubber plantations in southern Laos. Issue 1 (3rd September 2018) - Baird, Ian G.; Noseworthy, William; Tuyen, Nghiem Phuong; Ha, Le Thu; Fox, Jefferson
Abstract : Since the early 2000s the Lao government has dramatically increased the number of large‐scale land concessions issued for agribusinesses. While studies have documented the social and environmental impacts of land dispossession, the role of Vietnamese labour on these Vietnamese‐owned rubber plantations has not previously been investigated. Taking a political ecology approach, we situate this study at the intersection between 'land grabbing' studies and work on 'labour geographies'. Most of the remittances generated from Vietnamese working in Laos are used for non‐agricultural purposes, with people purposely choosing to not invest in agriculture in Vietnam. Vietnamese labour on Lao plantations still has significant spatial implications, both in Laos and in Vietnam, including through the norms, formal rules and practices introduced at rubber plantations by Vietnamese workers and management, but also through labour regime changes in Vietnam. In Laos, one of the most significant results has been to make certain spaces less welcoming to Lao labour. This study particularly points to the importance of geopolitics, as the close political relationship between Laos and Vietnam, and the fact that Vietnamese companies and managers are involved, is crucial for understanding the particular nature of the labour geographies associated with Vietnamese rubber plantations in Laos.